Elementary School Student S Narratives: Two Writing Tasks [Narraciones de Escolares Básicos: Dos Tareas de Escritura] - Rubio-Manriquez, M (Universidad Catolica Silva Henriquez, 2016)
The aim of this article is to describe the validation process of two writing tasks and a preliminary analysis of texts produced by 3°, 5° and 7° elementary school students. The two tasks are carried out by a total of 275 children. The results show that if narrative is defined in broad terms (as a sequence of actions in time) all students manage to produce these sort of texts. However, if defined in restrictive terms (as a sequence of events which are articulated around problem solving), spontaneous writing achieves a higher level of achievement due to the fact that the memory and order of images engage most of students attention in the second condition. It can be concluded that both tasks are appropriate for children from a variety levels of elementary education and their production of relatively coherent texts. © 2016 Universidad Catolica Silva Henriquez. All rights reserved.